REINTERPRETASI DARI PROGRAM PEMBINAAN KE PEMBERDAYAAN DALAM PELESTARIAN EKOLOGI SUKU TERASING DI INDONESIA (STUDI KASUS SUKU KUBU DI SUMATERA) - Syuroh, Mat (Bumi Lestari; Vol 11 No 1 (2011), 2011)
This research was conducted to determine the ecology of the Kubu tribe concerning the environment, and profile characteristics of life, including social structure, culture and philosophy of life Kubu tribe living in the jungle in Banyuasin regency, South Sumatra. The research method used in qualitative research is descriptive. Data collection used by observation field study, namely: interviews, archival research and literature study. As for the hypothesis of social anthropology model Radcliffe-Brown and Malinowski that tribal cosmology associated with the inner world tribe and the outside world inhabited by people of traditional post. In reality on the ground, since 2004 there have been many ecological changes around the Kubu tribe Batang Hari Leko Banyuasin District. Changes that occurred include execution of programs by the government’s transmigration land-clearing, land clearance by plantation companies and the coming of a large number of nomads who lead traditional ecological Kubu tribe becomes narrower
Keywords: forest; Kubu tribe; ecology change